2019
DOI: 10.1007/s00330-019-06420-4
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging in discriminating between benign and malignant paediatric ovarian masses: a systematic review

Abstract: Objectives The use of magnetic resonance (MR) imaging in differentiation between benign and malignant adnexal masses in children and adolescents might be of great value in the diagnostic workup of sonographically indeterminate masses, since preserving fertility is of particular importance in this population. This systematic review evaluates the diagnostic value of MR imaging in children with an ovarian mass. Methods The review was made according to the PRISMA Statement. PubMed and EMBASE were systematically se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…They showed that most of the malignant ovarian masses and some of the dermoid cysts had high intensity on DWI. Most of the benign lesions had low signal intensity on DWI [6] [18] [19].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that most of the malignant ovarian masses and some of the dermoid cysts had high intensity on DWI. Most of the benign lesions had low signal intensity on DWI [6] [18] [19].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, conventional MRI suggested malignant pathology in three masses; all proved to be malignant. An increased risk of malignancy was related to increased size of the lesion, increased wall thickness, presence and increased size of vegetation, mixed cystic and solid configuration, intermediate to high intensity on T2-weighted imaging, presence of contrast enhancement and of ascites or peritoneal implants [4,12]. MRI also suggested borderline pathology in four masses, two of them were truly borderline tumors, while one of them was proven to be benign and the last was histopathologically proven malignant.…”
Section: Discussionmentioning
confidence: 99%
“…The use of Magnetic Resonance (MR) imaging in differentiation between benign and malignant adnexal masses might be of great value in the diagnostic workup of sonographically indeterminate cystic lesions, since preserving fertility is of particular importance [4].…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative investigations for a child referred with a suspected benign ovarian tumor : Any patient with a complex ovarian lesion or an ovarian cyst >5 cm should undergo an ultrasound (US) scan as the first‐line investigation 19,20 For further assessment of the mass, the patient should have an abdomino‐pelvic magnetic resonance imaging (MRI) scan 19,21,22 Any patient with a complex ovarian lesion or simple ovarian cyst > 5 cm should have the serum tumor markers alpha fetoprotein (AFP) and beta human chorionic gonadotropin (beta‐HCG) assayed.…”
Section: Methodsmentioning
confidence: 99%